2022
DOI: 10.1021/acsanm.1c03682
|View full text |Cite
|
Sign up to set email alerts
|

Composites of Co-Doped Graphitic C3N4 Nanosheets and TiO2 Nanoparticles for Electrorheological Fluid Applications

Abstract: Herein, composites of Co-doped graphitic C3N4 nanosheets and TiO2 nanoparticles (Co-C3N4 NSs/TiO2 NPs) were prepared through a two-step synthetic strategy, and their electrorheological (ER) performance under varied electric field strengths was also researched. The microstructure, chemical elements, and surface morphology of materials were studied thoroughly by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray powder diffraction (XRD), Fourier transform infrared (FTIR) spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Figure S7 presents the bonding energy of C 1s and O 1s in Pt/ g -C 3 N 4 , Pt/ pyrrol -N x C, Pt/ ani -N x C, Pt/ pyridine -N x C, and Pt/ ben -C. The spectrum of C 1s could be deconvoluted into six species at 284.8, 285.8, 286.9, 287.7, 288.1, and 288.9 eV, which were corresponding to C–C/C–N/CC, CN, C–O, CO, N–CN, and O–CC, respectively. the peak at 532.3 eV in O 1s could be assigned to C–O/CO species, and other peaks at 531.3 and 533.6 eV were attributed to −OH and O 2 , respectively, which might be derived from the adsorbed oxygen on the catalyst surface …”
Section: Resultsmentioning
confidence: 99%
“…Figure S7 presents the bonding energy of C 1s and O 1s in Pt/ g -C 3 N 4 , Pt/ pyrrol -N x C, Pt/ ani -N x C, Pt/ pyridine -N x C, and Pt/ ben -C. The spectrum of C 1s could be deconvoluted into six species at 284.8, 285.8, 286.9, 287.7, 288.1, and 288.9 eV, which were corresponding to C–C/C–N/CC, CN, C–O, CO, N–CN, and O–CC, respectively. the peak at 532.3 eV in O 1s could be assigned to C–O/CO species, and other peaks at 531.3 and 533.6 eV were attributed to −OH and O 2 , respectively, which might be derived from the adsorbed oxygen on the catalyst surface …”
Section: Resultsmentioning
confidence: 99%
“…Flow curves of Glu-600- and Glu@SiO 2 -based fluids demonstrated that typical shear stress plateau at low shear rates. For that reason, the ER activity of the fluids was evaluated using the six-parameter Cho–Choi–Jhon (CCJ) model, which properly describes ER behavior at a wide shear rate region and can be read as follows τ = τ 0 1 + false( t 2 γ̇ false) α + η ( 1 1 + ( t 3 γ̇ ) β ) γ̇ where τ denotes the shear stress, τ 0 represents the dynamic yield stress, γ̇ is the shear rate, t 2 and t 3 are time constants, α is the parameter related to the initial decrease in stress, and η ∞ is the viscosity at high γ̇, while β can be considered as the corrective term, attaining 0 < β ≤ 1. Figure A–C shows that the experimental data were fitted with the CCJ model (eq ) for the fabricated (5 wt %) ER fluids with high accuracy ( R 2 > 0.94).…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peak at 13.1°c orresponded to the (100) plane due to the planar structure of the triazine unit. 27,28 For the WO 3 material, all characteristic diffraction peaks could be retrieved as the WO 3 (JCPDS no. 83-0950) monoclinic crystal structure.…”
Section: Resultsmentioning
confidence: 99%